Humanising health and social care support for people with intellectual and developmental disabilities: Protocol for a scoping review - Meinert,E (JMIR Research Protocols, 2022)
Background:Healthcare is shifting towards a more person-centred model, however, people with intellectual and developmental disabilities can still experience difficulties in accessing equitable healthcare. Given these difficulties, it is important to consider how principles such as empathy and respect can be best incorporated into health and social care practices for people with intellectual and developmental disabilities, to ensure they are receiving humanising and equitable treatment and support.Objective:The purpose of this scoping review is to provide an overview of the current research landscape and knowledge gaps regarding the development and implementation of interventions based on humanising principles that aim to improve health and social care practices for people with intellectual and developmental disabilities.Methods:The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) and Population, Intervention, Comparator, Outcome, and Study (PICOS) frameworks will be used to structure the review. Six databases (PubMed, MEDLINE, Embase, CINAHL, PsycInfo, and Web of Science) will be searched for articles published in English in the previous 10 years that describe or evaluate health and social care practice interventions under-pinned by humanising principles of empathy, compassion, dignity, and respect. Two reviewers will collaboratively screen and select references based on the eligibility criteria and extract the data into a predetermined form. A descriptive analysis will be conducted to summarise the results and provide an overview of interventions in three main care areas: health care, social care, and informal social support.Results:Results will be included in the scoping review, which will be submitted for publication by June 2022.Conclusions:This scoping review will summarize the state of the field of interventions that are using humanising principles to improve health and social care for adults with in